2014
DOI: 10.1186/1475-2875-13-152
|View full text |Cite
|
Sign up to set email alerts
|

High levels of sulphadoxine-pyrimethamine resistance Pfdhfr-Pfdhps quintuple mutations: a cross sectional survey of six regions in Tanzania

Abstract: BackgroundIn 2006, the first-line anti-malarial drug treatment in Tanzania was changed from sulphadoxine-pyrimethamine (SP) to artemether-lumefantrine (ALu), an artemisinin-based combination (ACT), since when the use of SP has been restricted for intermittent preventive treatment in pregnancy (IPTp). A number of Plasmodium falciparum mutations are known to be associated with resistance to SP, but it is not known if the prevalence of these mutations is increasing or decreasing under the conditions of reduced le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 37 publications
(43 reference statements)
2
42
2
Order By: Relevance
“…The overall prevalence of single SNPs and as well, the resulting triple 86-184-1246 haplotype YFY haplotype was highest in Tanga. Interestingly, this coincides with highest prevalence of SP resistance markers also documented in Tanga region [25,28,29]. The haplotype YFY is linked to AQ and CQ resistance [21].…”
Section: Discussionmentioning
confidence: 67%
“…The overall prevalence of single SNPs and as well, the resulting triple 86-184-1246 haplotype YFY haplotype was highest in Tanga. Interestingly, this coincides with highest prevalence of SP resistance markers also documented in Tanga region [25,28,29]. The haplotype YFY is linked to AQ and CQ resistance [21].…”
Section: Discussionmentioning
confidence: 67%
“…Mutations at codon 613S have been documented in Africa (13). In Tanzania, the prevalence of a triple Pfdhfr mutation was recently found to be Ͼ84% in all regions, whereas prevalence of the Pfdhps double mutation ranged from as low as 43.8 to 95% (14). Recently, studies in some countries of East Africa have observed the emergence of the Pfdhps 581G mutation with quintuple mutants, resulting in sextuple mutants (15).…”
mentioning
confidence: 99%
“…To this end, a number of bepotastine-based sulphonamides were synthesized, as both these compound classes are known to efficiently inhibit parasitic development. 7,8 Subsequently, these compounds were tested to establish their inhibitory potential on the asexual stages of human malaria parasite. To prioritize potential antimalarial scaffolds within the synthesized library, we conducted preliminary screening experiments, based on which the ten most active molecules were selected for detailed analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In combination with pyrimethamine, folic acid antagonists such as sulfadoxine were widely used for malaria treatment; however resistance against this combination has been reported extensively. 7 Histamine-1 receptor antagonists like bepotastine were shown to be effective against the proliferation of Plasmodia both in vitro and in vivo. Thus, we designed and evaluated novel chemical scaffolds, which combine the structural features of both sulphonamides and bepotastine, against the asexual developmental stages of P. falciparum.…”
Section: Introductionmentioning
confidence: 99%